METHODOLOGY OF TEACHING ELEMENTARY SCHOOL STUDENTS TO MULTIPLICATION AND DIVISION OUTSIDE THE TABLE - Mamasoliyeva Muqaddam Abdumannob qizi (PEDAGOGS, 2024)
Annotations: In the article, the authors analyze different methodological approaches to the out of the table multiplication and division’s study in primary school. The above analysis reveals the peculiarities of organizing the junior schoolchildren’s educational activity in mastering the skills and abilities for these calculation’s cases. Updated and compared in the framework of different training systems: traditional and developing.